2017
DOI: 10.1007/s11748-017-0825-6
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of primary lung cancer in a solitary pulmonary lesion after a previous malignancy

Abstract: A combination of radiological findings, smoking history, and type of previous malignancy can improve the ability to predict primary lung cancer in the presence of a solitary pulmonary lesion that appears after previous treatment for a malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Size and SUV max of the PLs were investigated as predictive factors of NLC; some sources stated (<3 cm) smaller lesions 29 while several others expressed that larger lesions (>3 cm) were more frequent in their studied NLC groups. 17 Nakadate et al revealed that NLC patients had significantly larger PLs, which also have significantly higher SUV max uptakes than PM patients. 17 In our study, NLC patients with a prior extrapulmonary malignancy had significantly greater tumor size (>2 cm) and significantly higher SUV max values (>5 g/mL) (p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Size and SUV max of the PLs were investigated as predictive factors of NLC; some sources stated (<3 cm) smaller lesions 29 while several others expressed that larger lesions (>3 cm) were more frequent in their studied NLC groups. 17 Nakadate et al revealed that NLC patients had significantly larger PLs, which also have significantly higher SUV max uptakes than PM patients. 17 In our study, NLC patients with a prior extrapulmonary malignancy had significantly greater tumor size (>2 cm) and significantly higher SUV max values (>5 g/mL) (p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…17 Nakadate et al revealed that NLC patients had significantly larger PLs, which also have significantly higher SUV max uptakes than PM patients. 17 In our study, NLC patients with a prior extrapulmonary malignancy had significantly greater tumor size (>2 cm) and significantly higher SUV max values (>5 g/mL) (p < 0.05). Since the smaller malignant nodules mostly have a lower SUV max value than the larger malignant nodules, 35 it is possible that NLC patients have greater SUV max values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of radiological findings, smoking history, and type of previous malignancy can reportedly improve the ability to predict primary lung cancer in the presence of a solitary pulmonary lesion that appears after treatment for a previous malignancy (17). The actual frequency of the diagnosis of SPN is also useful information.…”
Section: The Evaluation Of Pulmonary Nodules In Patients With a History Of Malignancymentioning
confidence: 99%
“…Our evaluation of the prognostic significance of GGOs was restricted to patients with a prior history of lung cancer. Although several studies have assessed the likelihood of identifying a malignant lesion during GGO resection among patients with prior malignant lesions [27][28][29], ours is the first study to describe the natural history of GGO in patients with a history of only lung cancer.…”
Section: Commentmentioning
confidence: 99%